2021
DOI: 10.1371/journal.ppat.1009670
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA KIKAT/LINC01061 as a novel epigenetic regulator that relocates KDM4A on chromatin and modulates viral reactivation

Abstract: KDM4A is a histone lysine demethylase that has been described as an oncogene in various types of cancer. The importance of KDM4A-mediated epigenetic regulation in tumorigenesis is just emerging. Here, by using Kaposi’s sarcoma associated herpesvirus (KSHV) as a screening model, we identified 6 oncogenic virus-induced long non-coding RNAs (lncRNAs) with the potential to open chromatin. RNA immunoprecipitation revealed KSHV-induced KDM4A-associated transcript (KIKAT)/LINC01061 as a binding partner of KDM4A. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…One of them was ATOM , which encodes angiomotin, a protein that promotes cell migration and angiogenesis. In accordance, overexpression of KIKAT/LINC01061 in SLK cells induced cell migration [ 317 ]. Hence, KSHV-induced expression of KIKAT/LINC01061 may play a role in KSHV’s pathogenicity.…”
Section: Oncoviruses and Long Non-coding Rnasmentioning
confidence: 91%
“…One of them was ATOM , which encodes angiomotin, a protein that promotes cell migration and angiogenesis. In accordance, overexpression of KIKAT/LINC01061 in SLK cells induced cell migration [ 317 ]. Hence, KSHV-induced expression of KIKAT/LINC01061 may play a role in KSHV’s pathogenicity.…”
Section: Oncoviruses and Long Non-coding Rnasmentioning
confidence: 91%
“…The KSHV-lytic protein (K-Rta) induces the expression of a cellular lncRNA KIKAT/LINC01061 (KSHV-Induced KDM4A-Associated Transcript) [ 68 ]. Yang et al showed that KIKAT interacts with a histone lysine demethylase (KDM4A) and re-localizes KDM4A from the transcription start site (TSS) of the Angiomotin (AMOT) gene.…”
Section: Chromatin–lncrna Interactions Regulate Viral Infectionsmentioning
confidence: 99%
“…Yang et al showed that KIKAT interacts with a histone lysine demethylase (KDM4A) and re-localizes KDM4A from the transcription start site (TSS) of the Angiomotin (AMOT) gene. The KIKAT -mediated relocation of KDM4A increased the AMOT transcription and angiomotin-dependent cell migration, thus implicating its role in angiogenesis in Kaposi’s sarcoma [ 68 ]. KIKAT was also shown to enhance KSHV reactivation.…”
Section: Chromatin–lncrna Interactions Regulate Viral Infectionsmentioning
confidence: 99%
See 2 more Smart Citations